Asuhan Keperawatan Pola Napas Tidas Efektif Pada Bayi Dengan Rds (Respiratory Distress Syndrom) Diruang Nicu Rsud Dr. Soegiri Lamongan - Yuan Bagus Dwi S.S (2020)
Preliminary. Respiratory syndrome (respiratory distress syndrome, RDS) is a term used for respiratory dysfunction in neonates. This disorder is a disease associated with delayed development of lung maturity or inadequate amount of surfactant in the lungs. Respiratory disorders and disorders are the main causes of neonatal death (35.9%), then prematurity (42.4%) and sepsis (12%). The purpose of this study is to apply nursing care patterns of ineffective breath in the NICU room Dr. Soegiri Lamongan. Method Descriptive design with a case study approach through interviews, observation, physical examination and home visits Results. From the results of the study found 2 nursing diagnoses found that ineffective breath patterns associated with respiratory fatigue and gas exchange disorders associated with prematurity. Discussion The results of the case study show that there is a gap between the case review and the literature on the assessment aspect, namely physical examination. Nursing diagnoses that appear are ineffective breathing patterns. Interventions are emphasized on monitoring respiration. The final evaluation was reached on day 3 ie the gas exchange disturbance was resolved. Conclusion Nursing care for infants A with RDS. all nursing diagnoses can be carried out according to interventions that have been determined to overcome the above nursing problems can be done optimally. Suggestion for institutions to provide supporting literature in carrying out case studies especially with regard to RDS, and for writers to increase knowledge in providing nursing care